Zawieranie małżeństw przez osoby z niepełnosprawnością intelektualną i psychiczną w prawie polskim a konwencja ONZ o prawach osób niepełnosprawnych: [Contracting marriage by persons with intellectual and mental disabilities according to polish law and the Convention on the rights of persons with disabilities] (Studia Prawnicze / The Legal Studies, 2013)
Jedną z podstawowych zasad polskiego prawa rodzinnego jest ochrona rodziny i małżeństwa. Zasada ta ma rangę normy konstytucyjnej – art. 18 Konstytucji RP stanowi m.in., że małżeństwo i rodzina znajdują się pod opieką i ochroną Rzeczpospolitej Polskiej.Zasada ta tradycyjnie jest ujmowana jako postulat (obowiązek) takiego ukształtowania poszczególnych instytucji prawnych, aby zapewnić małżeństwu i rodzinie na niej opartej optymalną realizację funkcji, które ustawodawca uznaje za najbardziej istotne dla społeczeństwa. Analiza poszczególnych instytucji prawa rodzinnego prowadzi do wniosku, że najważniejsze dla ustawodawcy są funkcje prokreacyjna i opiekuńczo-socjalizacyjna w stosunku do dzieci. According to Polish legal system it is not possible for persons affected by „mental illness” or „mental retardation” to marry (article 12 Family and Guardianship Code). As an exception to this rule, the Court may authorize the conclusion of such marriage, if the person’s condition does not put „marriage” or „the future health of the off spring” in hazard. This adjustment was justified by the traditional understanding of the principle of the protection of marriage and family, concern about the lack of „capability” of the patient to meet one’s marriage commitments, the recognition of lack of parental competences in people with mental disabilities and mental illness, and the danger of „transferring” the illness to the children of parents. Acts of international law provide for a different design, accenting the right to marry and to found a family (article 12 European Convention on Human Rights). For people with disabilities, article 23 of the Convention on the Rights of Persons With Disabilities which guarantees the right to marry and to found a family of all persons with disabilities, including mental and intellectual, is of particular importance. The conventional solutions analysis leads to the conclusion that not only the current article 12 Family and Guardianship Code is contrary to the Convention but to establish similar restrictions based on the health status of the betrothed could be regarded as discriminatory and contrary to the Convention. It should be noted that the progressive interpretation of the Convention on the Rights of Persons with Disabilities can lead to conflicts between solutions of the act of international law and the national rules of family law which are based on the traditionally understood principles of the protection of the family and child welfare. It is therefore necessary to find solutions and develop compromise in the process of adaptation of Polish law to the requirements of conventional solutions.